2015
DOI: 10.1016/j.scitotenv.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparing catchment sediment fingerprinting procedures using an auto-evaluation approach with virtual sample mixtures

Abstract: Information on sediment sources in river catchments is required for effective sediment control strategies, to understand sediment, nutrient and pollutant transport, and for developing soil erosion management plans. Sediment fingerprinting procedures are employed to quantify sediment source contributions and have become a widely used tool. As fingerprinting procedures are naturally variable and locally dependant, there are different applications of the procedure. Here, the auto-evaluation of different fingerpri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 48 publications
2
57
0
Order By: Relevance
“…While the use of fallout radionuclides in sediment fingerprinting has helped to assess the time passed since the sediment eroded (residence time) (e.g. Palazón et al, 2015;Smith and Blake, 2014;Wilkinson et al, 2015), it remains a challenge to interpret patterns in sediment source contributions in terms of catchment erosion processes.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…While the use of fallout radionuclides in sediment fingerprinting has helped to assess the time passed since the sediment eroded (residence time) (e.g. Palazón et al, 2015;Smith and Blake, 2014;Wilkinson et al, 2015), it remains a challenge to interpret patterns in sediment source contributions in terms of catchment erosion processes.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…One of the methodological differences within the range of different applications of the sediment fingerprinting procedure in the literature is related to the statistical analysis used to identify the subset of the tracer properties which 'best' discriminate between sources (Palazón et al, 2015b). Although the two step process outlined by Collins et al (1997) which combined Kruskal-Wallis H-test as first step and discriminant function analysis as second step has been extensively used in source fingerprinting studies (e.g., Russell et al, 2001;Minella et al, 2008;Hughes et al, 2009;Schuller et al, 2013;Stone et al, 2014), other procedures have been used to select the most effective optimum composite fingerprint, such as the use of principal component analysis (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the fingerprints should provide a clear distinction between the sources of sediment identified. However, recent research by Palazón et al (2015) demonstrated that different fingerprint selection methods yielded different subsets of fingerprint properties that were able to successfully discriminate between different potential sources of sediment and that the method of fingerprint selection ultimately influenced the sediment apportionment results. Furthermore, if the fingerprints are unable to provide good discrimination between potential sources then the sources may need to be grouped together (Section 1.3.1).…”
Section: Fingerprint Selection Processmentioning
confidence: 99%
“…Recent work by Palazón et al (2015) showed that the subset of tracers selected was dependent on the procedure used and that each subset of selected tracers resulted in different apportionment results. Furthermore, a purely statistical approach may not be the most appropriate method, as the conservative behaviour of sediment fingerprints during transport through the watershed or the underlying processes that lead to their ability to discriminate between sources are not considered Sherriff et al 2015).…”
Section: Fingerprint Selectionmentioning
confidence: 99%
See 1 more Smart Citation